1993
DOI: 10.1523/jneurosci.13-04-01346.1993
|View full text |Cite
|
Sign up to set email alerts
|

Changes in protein synthesis accompanying long-term potentiation in the dentate gyrus in vivo

Abstract: The possibility that the induction of long-term potentiation (LTP) is followed by changes in protein synthesis has been examined using high- resolution two-dimensional gel electrophoresis. 35S-methionine, infused into the third ventricle of anesthetized rats, was used to label hippocampal proteins. LTP was induced unilaterally in the dentate gyrus by tetanic stimulation of the perforant path, and followed either for 1 hr or for 3 hr. Two-dimensional gel autoradiographs were quantitatively analyzed using the PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…Our localization of FMRP to the spine heads and bases raises the possibility that the spine dysmorphisms occurring in fragile X are related to local alterations in protein translation attributable to the loss of FMRP. It has been proposed that postsynaptic mRNAs and ribosomes may serve to synthesize components required for synapse development and plasticity (Steward and Levy, 1982;Steward, 1983;Steward and Falk, 1986) and for the induction and maintenance of long-term potentiation (Frey et al, 1991;Fazeli et al, 1993). Although direct evidence does not yet exist, we speculate that altered protein synthesis in dendrites and spines occurs in fragile X, leading to synaptic dysfunction and mental retardation.…”
Section: Fragile X Syndrome and Fmrpmentioning
confidence: 66%
“…Our localization of FMRP to the spine heads and bases raises the possibility that the spine dysmorphisms occurring in fragile X are related to local alterations in protein translation attributable to the loss of FMRP. It has been proposed that postsynaptic mRNAs and ribosomes may serve to synthesize components required for synapse development and plasticity (Steward and Levy, 1982;Steward, 1983;Steward and Falk, 1986) and for the induction and maintenance of long-term potentiation (Frey et al, 1991;Fazeli et al, 1993). Although direct evidence does not yet exist, we speculate that altered protein synthesis in dendrites and spines occurs in fragile X, leading to synaptic dysfunction and mental retardation.…”
Section: Fragile X Syndrome and Fmrpmentioning
confidence: 66%
“…These results suggest that critical phosphorylation events for LTP occur during the first 20 min after induction stimuli and ongoing protein kinase activity is not required during the later (30--80 min) stages of LTP. Increasing evidence indicates that phosphorylated substrates (e.g., B-50; Gianotti et al 1992;and AMPA receptor;Davies et al 1989) and new proteins (Otani et al 1992;Fazelli et al 1993) …”
Section: Discussionmentioning
confidence: 99%
“…However, actinomycin D, an inhibitor of mRNA synthesis, exerted no significant effect during the first 3 h after tetanus (168, 474), although an inhibitory effect was observed after Ïł5 h (168), suggesting a dependence on transcription and translation at this time. Interestingly, there was evidence of newly synthesized proteins in the extracellular medium 3 h after induction of LTP (155), while increased synthesis of presynaptically located proteins was also reported within this time frame (359). Similar temporally distinct phases were distinguished with respect to learning in 1980 when it was reported that intrahippocampal injection of the protein synthesis inhibitor anisomycin inhibited retention in a brightness discrimination task but that the inhibition only occurred if the drug was administered before training or several hours after training; injection of anisomycin shortly after training failed to affect retention (206).…”
Section: F Protein Synthesis and Ltpmentioning
confidence: 99%